(untitled) (Linguostylistic Studies, 2021)
The article elucidates the analysis of legal language used in the courtroom settings. In the focus are specific features of the narrative in US courtroom discourse. The study has proved that the use of the narrative in courtroom discourse is dependent on the peculiarities of social, pragmatic, and linguistic contexts. In terms of this approach, sustainable and variable features of the courtroom narration are distinguished. They include: 1) the theme of the story – the courtroom narration is a story about the circumstances of the crime, the defendant, or the victim; 2) the aims of the participants – they are contradictory for the prosecutor because it is a kind of competition, a battle of narratives in which the strongest one wins; 3) the speech etiquette; 4) the intertextual links of the courtroom narration – it always appeals to real facts and normative texts (laws, criminal code); 5) whether the system is competitive or non-adversarial. The attributes are, firstly, communicative strategies, tactics, stratagemes, the non-verbal expression, secondly, social stereotypes relevant to the historical era in which the trial takes place, and thirdly, the value priorities of the country. The study has revealed that the content of the prosecutors’ and lawyers’ narrative is different. The prosecutors’ narrative is characterised by the following features: an appeal to the ideological attitudes of society during the relevant historical period (social context); the use of a detailed strategy with an emphasis on the guilt of the defendants; the use of manipulative tactics and the actualisation of the stratagems “empathy”, “figurative evaluation” and “concealing specific facts” (pragmatic context); syncretism of the functions of the narration and the persuasion; extensive use of emotive means of language; implicit opposition of the symbols of “protection”, “life values” – “murder” (linguistic context). The specificity of the lawyer’s narrative is determined by the following attributes: reliance on the value priorities of society, including those associated with the attribute of professionalism (social context); the use of the tactics of approaching the audience; communicative tactics of appeal to common moral values; and the stratagems “empathy”, “imaginative assessment” and “rational assessment” (pragmatic context); the two-pronged orientation of the narrative; the actualisation of associative semantic components of the meanings of words and phrases, semantic evaluation, the repetition of words that emphasise the main priorities of society (linguistic context).